Is dry bulk shipping still worth investing in? - De Almeida, Devinda Iroshan (2017)
The “perfect competition” nature of the dry bulk industry coupled with the current depressed market, has seen several new entrants such as operators who operate on an asset-light business model and avoid the financial burden of asset-heavy business models undertaken by ship owners. Despite the clear difference, it is yet distinguishable as to which business model would be more beneficial in this current depressed market. Past literatures have conducted evaluations of both business models in constructive measures, but only in isolation. In this paper, comparisons shall be attempted in both quantitative and qualitative approaches to differentiate each business model for identifying perhaps, the superior business model. Quantitatively, historical market data from the relevant shipping markets were collated to calculate and compare net time charter margins for both ship owners and operators. Qualitatively, opinions from ship owners and operators were also collated to conduct a comparison in terms of risk management in dry bulk shipping. The combined results of the comparison could prove helpful in identifying the pros and cons of both business models and hopefully propose a viable option for investors to take up in this current depressed market.